BdMO(Regional) 2012 Problem

Geometry Level 3

In a circle, A B = 4 AB=4 is the diameter and O O is the centre. C C and D D are chosen such that C , O , D C,O,D are co-linear, C O B = A O D = 3 0 \angle COB= \angle AOD=30^\circ , O C = O D OC=OD and B C O = 9 0 \angle BCO = 90^\circ . The perpendicular on A B AB through O O meets A C AC at E E and B D BD at F F .

If E F = a b c EF=\frac{a\sqrt{b}}{c} where a , b , c a,b,c are integers and b , c b,c are primes, find the value of a + b + c a+b+c .

Note: C C and D D are not necessarily on the circumference of the circle.


The answer is 14.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

10 solutions

BdMO BdMO

In B O C , sin O B C = O C O B sin 6 0 = O C 2 O C = 3 \triangle BOC, \sin OBC = \frac{OC}{OB} \rightarrow \sin 60^\circ = \frac{OC}{2} \rightarrow OC = \sqrt{3}

Draw a perpendicular C M CM from point C C on A B AB .

In O C M , sin C O M = C M O C sin 3 0 = C M 3 C M = 3 2 \triangle OCM,\sin COM = \frac{CM}{OC} \rightarrow \sin 30^\circ = \frac{CM}{\sqrt{3}} \rightarrow CM = \frac{\sqrt{3}}{2}

cos C O M = O M O C cos 3 0 = O M 3 O M = 3 2 \cos COM = \frac{OM}{OC} \rightarrow \cos 30^\circ = \frac{OM}{\sqrt{3}} \rightarrow OM = \frac{3}{2}

In A C M , A C 2 = A M 2 + C M 2 = ( O A + O M ) 2 + C M 2 = ( 2 + 3 2 ) 2 + ( 3 2 ) 2 = 49 4 + 3 4 = 13 \triangle ACM, AC^2 = AM^2 + CM^2 = (OA+OM)^2 + CM^2 = (2+\frac{3}{2})^2 + (\frac{\sqrt{3}}{2})^2 = \frac{49}{4} + \frac{3}{4} = 13

A C = 13 AC = \sqrt{13}

In A O C , sin x sin A O C = O C A C sin x = 3 × sin 15 0 13 sin x = 3 2 13 \triangle AOC, \frac{\sin x}{\sin AOC} = \frac{OC}{AC} \rightarrow \sin x = \frac{\sqrt{3} \times \sin 150^\circ}{\sqrt{13}} \rightarrow \sin x = \frac{\sqrt{3}}{2\sqrt{13}}

cos x = 1 s i n 2 x = 1 3 52 = 49 52 = 7 2 13 \cos x = \sqrt{1-sin^{2}x} = \sqrt{1 - \frac{3}{52}} = \sqrt{\frac{49}{52}} = \frac{7}{2\sqrt{13}}

tan x = sin x cos x = 3 7 \tan x = \frac{\sin x}{\cos x} = \frac{\sqrt{3}}{7}

tan x = O E O A O E = O A tan x O E = 2 3 7 \tan x = \frac{OE}{OA} \rightarrow OE = OA\tan x \rightarrow OE = 2\frac{\sqrt{3}}{7}

E F = 2 O E = 4 3 7 EF = 2OE = 4\frac{\sqrt{3}}{7}

4 + 3 + 7 = 14 4+3+7=\boxed{14}

After finding CM = SQRT(3)/2 and OM = 3/2, consider the similar triangles AEO & ACM
EO/CM = AO/AM = 2/(3/2)....EO/{SQRT(3)/2}.....2 EO = 2SQRT(3)/(2 + 3/2)
EF = 2
EO = 2SQRT(3)/( 7/2) = 4SQRT(3)/ 7

Niranjan Khanderia - 7 years, 1 month ago

Log in to reply

WE SHOULD HAVE
EO/CM = AO/AM = 2/( 2+3/2) = .EO/{SQRT(3)/2}.
SORRY FOR THE MISTAKE.

Niranjan Khanderia - 7 years, 1 month ago

\boxed[14]

Mark Joshua Santos - 7 years ago
Eloy Machado
Apr 2, 2014

(Please consider Fahin points names above to follow my solution)

Triangle B C O BCO is a "half-equilateral-triangle" with "side" B O = 2 BO = 2 (radius). So, B C = 1 BC = 1 ("half-side") and C O = 3 CO = \sqrt { 3 } .

Because C M CM is a height of right triangle B O C BOC , we know B O C M = C B C O BO\cdot CM=CB\cdot CO and then we get C M = 3 2 CM = \frac { \sqrt { 3 } }{ 2 } . Applying Pythagorean Theorem at triangle C O M COM , we get O M = 3 2 OM = \frac { 3 }{ 2 } . Thus, A M = 7 2 AM = \frac { 7 }{ 2 } .

Triangles AEO and ACM are similar, so E O C M = A O A M \frac { EO }{ CM } =\frac { AO }{ AM } and we get E O = 2 3 7 EO = \frac { 2\sqrt { 3 } }{ 7 } . Since the symmetry of given construction, E F = 2 E O EF = 2EO , therefore, E F = 4 3 7 EF = \frac { 4\sqrt { 3 } }{ 7 } and the answer is 4 + 3 + 7 = 14 4 + 3 + 7 = \boxed{14} .

Nice, no trigo.

Chung Kevin - 7 years, 2 months ago

\boxed{14}

Mark Joshua Santos - 7 years ago
Ronak Agarwal
Jun 28, 2014

Try my geometry classic question Find the area . I'm sure u will enjoy this

For convenience, I would also like to borrow Shakkhor's diagram.

If C O B = 3 0 \angle COB = 30^\circ and O C B = 9 0 \angle OCB = 90^\circ , then C O B \triangle COB is a 3 0 6 0 9 0 30^\circ - 60^\circ - 90^\circ triangle with O B \overline{OB} as its hypotenuse and C B \overline{CB} as the short leg. 3 0 6 0 9 0 30^\circ - 60^\circ - 90^\circ triangles are a special kind of right triangle in that the measurement of the short leg is half of that of the hypotenuse and the measure of the longer leg is that of the short leg multiplied by 3 \sqrt{3} . Since O B \overline{OB} is a radius of O \bigcirc O which has a diameter of 4 4 , O B = 2 \overline{OB} = 2 , and since O B \overline{OB} is the hypotenuse of C O B \triangle COB , m C B = m O B 2 = 2 2 = 1 m\overline{CB} = \frac{m\overline{OB}}{2} = \frac{2}{2} = 1 and m O C = m C B × 3 = ( 1 ) ( 3 ) = 3 m\overline{OC} = m\overline{CB} \times \sqrt{3} = (1)(\sqrt{3}) = \sqrt{3} .

Let us construct point M M such that O B C M \overline{OB} \perp \overline{CM} . Now, C O M \triangle COM is also a 3 0 6 0 9 0 30^\circ - 60^\circ - 90^\circ triangle with O C \overline{OC} as the hypotenuse and C M \overline{CM} as the short leg. Since m O C = 3 m\overline{OC} = \sqrt{3} , m C M = m O C 2 = 3 2 m\overline{CM} = \frac{m\overline{OC}}{2} = \frac{\sqrt{3}}{2} and m O M = m C M × 3 = ( 3 2 ) ( 3 ) = ( 3 ) 2 2 = 3 2 m\overline{OM} = m\overline{CM} \times \sqrt{3} = (\frac{\sqrt{3}}{2})(\sqrt{3}) = \frac{(\sqrt{3})^2}{2} = \frac{3}{2} .

Consider triangles A M C \triangle AMC and A O E \triangle AOE . Since A A \angle A \cong \angle A and A M C A O E \angle AMC \cong \angle AOE , A M C \triangle AMC and A O E \triangle AOE are similar triangles. We can assume that the ratios of A M \overline{AM} to M C \overline{MC} and A O \overline{AO} to O E \overline{OE} are the same as they are corresponding sides of similar triangles. A O \overline{AO} is another radius of O \bigcirc O so A O = O B = 2 \overline{AO} = \overline{OB} = 2 . From the above, we can do the following:

m M C m A M = m O E m A O m M C ( m A O + m O M ) = m O E m A O 3 2 2 + 3 2 = m O E 2 3 2 4 2 + 3 2 = m O E 2 3 2 7 2 = m O E 2 ( 3 2 ) ( 2 7 ) = m O E 2 3 7 = m O E 2 2 3 7 = m O E \begin{aligned} \frac{m\overline{MC}}{m\overline{AM}} &= \frac{m\overline{OE}}{m\overline{AO}} \\ \frac{m\overline{MC}}{(m\overline{AO} + m\overline{OM})} &= \frac{m\overline{OE}}{m\overline{AO}} \\ \frac{\frac{\sqrt{3}}{2}}{2 + \frac{3}{2}} &= \frac{m\overline{OE}}{2} \\ \frac{\frac{\sqrt{3}}{2}}{\frac{4}{2} + \frac{3}{2}} &= \frac{m\overline{OE}}{2} \\ \frac{\frac{\sqrt{3}}{2}}{\frac{7}{2}} &= \frac{m\overline{OE}}{2} \\ (\frac{\sqrt{3}}{2})(\frac{2}{7}) &= \frac{m\overline{OE}}{2} \\ \frac{ \sqrt{3}}{7} &= \frac{m\overline{OE}}{2} \\ \frac{2\sqrt{3}}{7} &= m\overline{OE} \\ \end{aligned}

We now know how long O E \overline{OE} is. But to find the length of E F \overline{EF} , we have to find first m O F m \overline{OF} . Looking at the diagram, we can get a hunch that O E O F \overline{OE} \cong \overline{OF} . Consider triangles A O C \triangle AOC and B O D \triangle BOD . A O C \angle AOC and B O D \angle BOD are vertical angles formed by the intersection of A B \overline{AB} and C D \overline{CD} and thus A O C B O D \angle AOC \cong \angle BOD . Also, we already know that C O D O \overline{CO} \cong \overline{DO} and A O B O \overline{AO} \cong \overline{BO} . By that, A O C \triangle AOC and B O D \triangle BOD are congruent (by S A S SAS congruence) and A C O B D O \angle ACO \cong \angle BDO . Further, consider triangles E O C \triangle EOC and F O D \triangle FOD . Since the sets of points C C , O O , and D D , and E E , O O , F F are collinear, then E O C \angle EOC and F O D \angle FOD are vertical angles and are congruent to each other. It is already known that C O D O \overline{CO} \cong \overline{DO} . Finally, A C O E C O \angle ACO \cong \angle ECO , B D O F D O \angle BDO \cong \angle FDO and A C O F D O \angle ACO \cong \angle FDO . Thus, E O C \triangle EOC and F O D \triangle FOD are congruent (by A S A ASA congruence) and E O F O \overline{EO} \cong \overline{FO} .

Thus, m E F = m E O + m O F = m E O + m E O = 2 3 7 + 2 3 7 = 4 3 7 m\overline{EF} = m\overline{EO} + m\overline{OF} = m\overline{EO} + m\overline{EO} = \frac{2 \sqrt{3}}{7} + \frac{2 \sqrt{3}}{7} = \frac{4 \sqrt{3}}{7} . Finally, a = 4 a = 4 , b = 3 b = 3 , c = 7 c = 7 and a + b + c = 4 + 3 + 7 = 14 a + b + c = 4 + 3 + 7 = \boxed{14} .

Too long !!

Niranjan Khanderia - 7 years, 1 month ago
Anna Anant
Nov 17, 2014

EF=(4√3)/7 a + b + c = 4 + 3 + 7 = 14

Suhas Dinesh
Nov 1, 2014
  1. Join D to A. Since, ∠COB = ∠AOD with DO = OC and AO = OB; AD = CB and AC = DB.
  2. Thus, △AOD and △COB are congruent triangles. Also, △AOC and △DOB are congruent. So, ∠ODA = ∠BCO = 90° or AD||BC. Also, ∠CAO = ∠OBD. This indicates that AC and BD are parallel. Hence, ACBD is a parallelogram. Thus, AD=BC and AC=BD. From ∟△AOD, ∠OAD = 60° (Since, ∠AOD = ∠COB = 30°). In a 30°:60°:90° triangle, the sides are in the ratio 1:2:√3. Given AB=4, AO=OB=2. Also given, OC=OD = √3. Thus, AD = CB = 1.
  3. Now, drop a perpendicular from D to AB say DX. From ∟△ADX, cos30°= DX/1 or DX = (√3)/2. By Pythagorean theorem, AX = 1/2. Thus, XB = 3.5 or 7/2.
  4. From ∟△DBX, by Pythagorean theorem, DB = √((7/2)^2+((√3)/2)^2) = √13.
  5. Since, OF||XD, by AAA theorem, ∟△BOF and ∟△BXD are similar triangles. Thus, BO/BX = BF/BD = OF/XD or 2/3.5 = BF/√13 = OF/(√3/2). This gives, OF = (2√3)/7.
  6. Since ACBD is a parallelogram, with points E, O and F being collinear, OE=OF.
  7. Hence, EF = 2OE = 2OF = 2((2√3)/7) = (4√3)/7 = (a√b)/c. a, b, c are integers and b, c are primes.
  8. Or, a+b+c = 14.
Arum Damaieka
Aug 1, 2014

EF=(4√3)/7 a + b + c = 4 + 3 + 7 = 14

\boxed{14}

Good Question :)

Artur Zanon
Apr 2, 2014

Easy solution: Find CO through pitagoras in COB then find AC through cossine law in AOC. Call the area from EOC as A1 and the area of EOA as A2. A1 is the product of EOxOCxsin60º/2, and that makes 3/4xY, beeing Y the half of EF. A2 is AOxY/2, and that makes Y. We know now that the area of the triangle AOC is 7xY/4, but this same area can be found by multiplying AOxOCxsin(150)/2, and that makes sqrt(3)/2. So, we know that 7xY/4 is equal to sqrt(3)/2. Doing the math we find that Y = 2xsqrt(3)/7, and EF is 2xY. So EF is 4xsqrt(3)/7. a = 4, b = 3 and c = 7. The sum makes 14.

Since OB=2, and angles COB=30^ & CBO=60^, sines of these angles give CB=1 & OC=Sqrt 3. Now, in triangle AOC, the sum of angles OAC & OCA is 30^. Since angle ACD & CDB are equal therefore angle OAC = 30^-CDB. In triangle CDB, the base CD is 2 SQRT3, thus tan CDB=1/2 SQRT 3. Now, tan CAO= TAN (30^-CDB)=(1/SQRT 3 -1/2 SQRT 3)/(1+ 1/SQRT3 * 1/2 SQRT3) = SQRT3/7 = EO/AO. This yields EO=2 SQRT 3/7.... and since EF=2 EO, therefore it comes to be 4 SQRT 3/ 7. equating 4,3 & 7 with the unknowns a, b & c, we get the sum 4+3+7=14.

Shabihe Baqri - 7 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...